IDENTIFICATION OF DRIVING FACTORS FOR LAND COVER CHANGE BASED ON SPATIAL BINARY LOGISTIC REGRESSION MODEL IN THE DEVELOPMENT AREA OF EAST JAVA PROVINCE - Agastya Sansa, Dimas
Land availability is a limited resource. Whereas the necessity for land always increasing. Such conditions caused the land cover change phenomena. If it does not planned or controlled properly, the phenomena can give some bad impacts on the environment. Land cover change generally caused by some specific driving forces and influenced by the characteristic of corresponding region. The goal of this final project is to identify the driving forces of land cover change in the development region of East Java Province using binary logistic regression (BLR) model. BLR is a data analysis method used to find the causality between a dichotomous independent variable and polychotomous dependent variables. Dependent variables used in this research are distance from main road, distance from industrial center and economic center, elevation, slope, and population density. Result of this research shows the driving factors of land cover change in each development area are different. The different characteristics between the two regions, ranging from vital economic activities to geographical aspects, give rise to different factors driving land cover change. It is hoped that by identifying the driving factors of land cover change carried out in this final project can provide new knowledge and become a material for decision making by the authority for land cover change management in East Java Province.